KOMUNIKASI PESRSUASIF DA’I DALAM PEMBINAAN KEAGAMAAN NARAPIDANA (Studi pada Lembaga Pemasyarakatan Wanita Kelas II A Bandar Lampung) - Hariyanto Hariyanto (Jurnal Ilmu Dakwah, 2017)
This Research explains about the Implementation of Persuasive Communication Da’i religious conseling of prisoner at women class institute II A Bandar Lampung. This search uses descriptive qualitative approach. Da’i who do couching comes from Institutions and non-institutions. Da’i who comes two institutions from UIN Raden Intan Lampung and Dewan Dakwah Islam Indonesia. While da’i who come from non-institution only one person that is Ustadzah Hamidah Hasibuan. This findings of the field show that the persuasive communication of da’i in the religious estublishment of the psinores in the female class II A Bandar Lampung Institute both coming from institutions and non-institutions through five stages formulated with AIDDA. First, attention of the da’i involves some inmates to the ta’lim majlis event officer, using light language, initiating the delivery of the material by asking the news, chanting, sholawat, and vocal like KH.Zainuddin M.Z. Second, the interest of da’i convey the material of julisprudence, morals, tahsin iqra, qira’at al-qur’an and tailored to the request of inmates. Third, the desire that the da’i use the language of invitation, seduction, motivation sentensces and anticipate language that discredit. Fourth, decision the prisoners respond da’i in the form of question, vent, inmates feel the settlement  of mistakes. And last, the action that the psinore return to have the spirit of life like to read Iqra, Al-qur’an and carry out religious orderi such as prayer and fasting sunnah.